(untitled) (UNWE Yearbook, 2024)
Hybrid courses which combine the benefits of face-to-face and electronic modes of instruction have gained popularity in higher education as they can increase the motivation of the new generations of learners and hence the effectiveness of academic courses. The objective of the research presented is to provide a blueprint for developing hybrid ESP courses in the fields of economics and socio-political studies in order to deliver modern and effective instruction in specialised English at the University of National and World Economy, taking into account the realities of the world today. The study seeks to yield a reliable picture of the students’ attitudes and needs, and a model for course optimisation.